A introdução de conceitos algébricos em livros didáticos do 8º ano do ensino fundamental à luz dos registros de representação semiótica - Silva, Edson Benedito Antunes Angelo da (2012)
This study aims to determine how it is presented the introduction of algebraic concepts in textbooks of 8th year of elementary school, the three collections more adopted by public school teachers in the urban area of the city of Cuiabá, for work in the 2011 school year. We sought to identify the recommendations of the National Curriculum Parameters - NCP's - Mathematics - third and fourth cycles of Basic Education, in order to observe the recommendations regarding the content of Algebra, and study the criteria used by the Guide Textbook - PNLD/2011 - Mathematics - final years of elementary school to the analysis of collections approved for the triennium 2011/2013. We substantiate our studies in Theory Records Semiotic Representation developed by Raymond Duval, plus some theses and dissertations dealing with issues related to Textbook or Algebra. In his theory, Duval suggests the use of various records concerning the Representation Mathematics activity, namely the registration of natural language, the symbolic register, the record in algebraic language and graphic record. According to this theory, access to mathematical knowledge is through a constant exchange of one record to another, as well as the articulation made between these various records. The methodology is a qualitative approach, character bibliographical, documentary and interpretive. Our study observed that the introduction of algebraic concepts in selected textbooks, use is made of the records of natural language, the symbolic register, the algebraic language and graphic recording, but in isolation and not as suggested by the theory of Duval, in other words, performing an exchange of one record to another. We believe that the relevance of this work lies in the importance of content coupled with the significant role Algebra Textbook support teaching and as a source of permanent appointment for the student